PROFIL TOKSIKOLOGIS EKSTRAK DAUN TUMBUHAN BAKA-BAKA (Hyptis capitata Jacq.) PADA HATI TIKUS PUTIH (Rattus norvegicus) - Sitti Ayu; Wahyu Harso; Maghfirahtul Jannah (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Hyptis capitata Jacq. plant has been using for traditional medicine. Utilization of medicinal plant must always consider to given dose because of toxic effect when too much medicine is taken. The aim of this study was to measure the liver damage in rats caused by H. capitata Jacq. leave extract. Either 300 (P1), 600 (P2) or 900 (P3) µg/kgBW H. capitata Jacq. leave extract was given orally to rats every 24 hours during 14 days. Zero point five ml ethanol 96% was given daily (K-) and without given anything (K+) was also conducted as a control. Both macroscopic and microscopic of liver damage were assessed. The result showed that rats given P3 treatment had the highest liver damage. The liver damage in rats was not statistically significant difference between P3 and K- treatments. The lowest liver damage was in rats given K+ treatment. There was no significant difference between P1 and P2 treatments on rats liver damage. Utilization of medicinal plant as traditional medicine should always be consider to doses.